Incidence and Risk Factors Associated With 30-Day Readmission for Alcoholic Hepatitis. Issue 10 (November 2019) - Garg, Sushil K.; Sarvepalli, Shashank; Singh, Dupinder; Obaitan, Itegbemie; Peeraphatdit, Thoetchai; Jophlin, Loretta; Asrani, Sumeet K.; Shah, Vijay H.; Leise, Michael D.
Abstract : Background: Alcohol abuse and liver disease are associated with high rates of 30-day hospital readmission, but factors linking alcoholic hepatitis (AH) to readmission are not well understood. We aimed to determine the incidence rate of 30-day readmission for patients with AH and to evaluate potential predictors of readmission. Methods: We used the Nationwide Readmissions Database to determine the 30-day readmission rate for recurrent AH between 2010 and 2014 and examined trends in readmissions during the study period. We also identified the 20 most frequent reasons for readmission. Multivariate survey logistic regression analysis was used to identify factors associated with 30-day readmission. Results: Of the 61, 750 index admissions for AH, 23.9% were readmitted within 30-days. The rate of readmission did not change significantly during the study period. AH, alcoholic cirrhosis, and hepatic encephalopathy were the most frequent reasons for readmission. In multivariate analysis female sex, leaving against medical advice, higher Charlson comorbidity index, ascites, and history of bariatric surgery were associated with earlier readmissions, whereas older age, payer type (private or self-pay/other), and discharge to skilled nursing-facility reduced this risk. Conclusions: The 30-day readmission rate in patients with AH was high and stable during the study period. Factors associated with readmission may be helpful for development of consensus-based expert guidelines, treatment algorithms, and policy changes to help decrease readmission in AH.